Nutritional status and quality of table grapes cultivated in Submédio São Francisco Valley - Suellen R. V. da Silva; Fernando J. Freire; Jefrejan S. Rezende; Renato L. dos Santos; Jailson C. Cunha (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The cultivation of fruit trees is influenced by abiotic factors such as nutritional management. However, fertilizers are used in large amounts in vineyards, resulting in excess nutrients that can cause stress and reduce fruit quality. Calcium (Ca) is one of the most used nutrients in vineyards due to its effects on fruit quality. However, excess of Ca interferes with the distribution of Ca compounds in fruits, being a form of abiotic stress. The aim of this study was to evaluate the influence of the nutritional balance of table grape orchards on calcium nutrition and fruit quality. Nineteen table grape orchards were selected in the Submédio São Francisco Valley in 2019 and 2020 crops. The nutritional diagnosis was performed using the integrated diagnosis and recommendation system (DRIS) and the average nutritional balance index (NBIm) was calculated. The concentration of Ca-pectate, Ca-total, berry firmness, soluble solids, titratable acidity, soluble solids/titratable acidity ratio and dry matter were determined in the fruits. The nutritional diagnosis identified excess Ca in the orchards. The correlation between Ca-pectate and the average NBIm was negative, indicating that the Ca-pectate concentration is higher in vines that are more nutritionally unbalanced. However, the Ca-total in the fruit was not correlated with Ca-pectate. Ca-total and Ca-pectate were not correlated with berry firmness. Calcium nutrition is complex and highlights the importance of associating the assessment of nutritional balance with Ca in fruit quality to optimize the nutritional management of the grapevine.